2017
DOI: 10.1111/acel.12655
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in stem cell aging

Abstract: SummaryAging is responsible for changes in mammalian tissues that result in an imbalance to tissue homeostasis and a decline in the regeneration capacity of organs due to stem cell exhaustion. Autophagy is a constitutive pathway necessary to degrade damaged organelles and protein aggregates. Autophagy is one of the hallmarks of aging, which involves a decline in the number and functionality of stem cells. Recent studies show that stem cells require autophagy to get rid of cellular waste produced during the qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 30 publications
1
127
0
Order By: Relevance
“…Over the past decade, researchers have made tremendous progress in under- standing stem cell aging and the molecular mechanisms underlying this process [34]. Previous studies have also confirmed the extrinsic ingredients, and transplantation trials have identified the intrinsic components that cause an age-dependent decline in the number and function of stem cells [130].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, researchers have made tremendous progress in under- standing stem cell aging and the molecular mechanisms underlying this process [34]. Previous studies have also confirmed the extrinsic ingredients, and transplantation trials have identified the intrinsic components that cause an age-dependent decline in the number and function of stem cells [130].…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is one of the hallmarks of aging [34]. It is a constitutive pathway associated with damage to organelles and protein aggregates through a decline in the number and function of stem cells [ It has been assumed that reactive oxygen species (ROS) may lead to a loss of differentiation [43] [44] [45].…”
Section: Impact Of Stem Cell Senescence In Aging and Diseasesmentioning
confidence: 99%
“…Altogether, autophagy is critical for protein and cellular homeostasis. The exact mechanisms underlying decreased autophagy with aging are unclear; however, it has been noted that autophagy is decreased in aging stem cell niches in particular, contributing to decreased regenerative capacity (Revuelta and Matheu 2017). There are many proteins that are involved in the autophagy pathway and among them are cathepsins.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that excessive autophagy could be related to neuronal death in cerebral ischemia (Fornai et al, ; Kabuta, Suzuki, & Wada, ; Shi et al, ). In addition, autophagy is also related to cellular aging, survival, and proliferation (Cianfanelli & Cecconi, ; Codogno & Meijer, ; Revuelta & Matheu, ). Wang et al concluded that curcumin strongly repressed MSC differentiation into astrocytes and immature neurons when they were in supportive medium, and inhibited the apoptosis and cell cycle in MSCs in the suspension.…”
Section: Molecular and Cellular Mechanisms Of Curcumin On Stem Cellsmentioning
confidence: 99%
“…However, other studies have shown that excessive autophagy could be related to neuronal death in cerebral ischemia (Fornai et al, 2008;Kabuta, Suzuki, & Wada, 2006;Shi et al, 2012). In addition, autophagy is also related to cellular aging, survival, and proliferation (Cianfanelli & Cecconi, 2015;Codogno & Meijer, 2005;Revuelta & Matheu, 2017).…”
Section: Ormond Et Al In a Study Used Stem Cells Alone Or In Combinamentioning
confidence: 99%